2011
DOI: 10.1097/nmd.0b013e3182392bfb
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Posttraumatic Stress Disorder Numbing and Hyperarousal Symptom Clusters in the Prediction of Physical Health Status in Veterans With Chronic Tobacco Dependence and Posttraumatic Stress Disorder

Abstract: Smoking and PTSD are predictors of poor physical health status. This study examined the unique contribution of PTSD symptoms in the prediction of the SF-36 physical health status subscales accounting for cigarette smoking, chronic medical conditions, alcohol and drug use disorders, and depression. This study examined baseline interview and self-report data from a national tobacco cessation randomized, controlled trial (Veterans Affairs Cooperative Study 519) that enrolled tobacco-dependent veterans with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Additionally, our study lends further support to previously published findings that identified depression as a factor with a large effect on physical HRQoL (Aversa et al, 2012;Harder et al, 2011). In the omnibus model with childhood maltreatment, PTSD, and depression predicting physical HRQoL, only depression explained a significant proportion of the variance in HRQoL, 10% of the unique variance.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, our study lends further support to previously published findings that identified depression as a factor with a large effect on physical HRQoL (Aversa et al, 2012;Harder et al, 2011). In the omnibus model with childhood maltreatment, PTSD, and depression predicting physical HRQoL, only depression explained a significant proportion of the variance in HRQoL, 10% of the unique variance.…”
Section: Discussionsupporting
confidence: 77%
“…PTSR have consistently been associated with a broad spectrum of physical health problems in adult trauma survivors, such as musculoskeletal bodily pain, gastroenterological and cardiovascular symptoms (Asnaani, Reddy, & Shea, 2014;Bugge et al, 2017;Gupta, 2013;Harder et al, 2011). In the context of trauma exposure, researchers have suggested a neurobiological pathway linking PTSR to physical health problems, suggesting that PTSR activate the body's stress regulation system, leading to both overand underactivation of systems controlling immune and inflammation responses (Kearney et al, 2010).…”
Section: Ptsr and Physical Healthmentioning
confidence: 99%
“…For instance, Harder et al. () found that hyperarousal was significantly associated with most physical health domains in a sample of tobacco‐dependent veterans with chronic PTSD. However, this study was based on a relatively older population and was limited to participants with PTSD and nicotine dependence.…”
mentioning
confidence: 99%
“…Hyperarousal symptoms, such as poor sleep and persistent hypervigilance, are thought to negatively impact physical health given the way this particular cluster of symptoms interferes with body functioning. For instance, Harder et al (2011) found that hyperarousal was significantly associated with most physical health domains in a sample of tobacco-dependent veterans with chronic PTSD. However, this study was based on a relatively older population and was limited to participants with PTSD and nicotine dependence.…”
mentioning
confidence: 99%
See 1 more Smart Citation